Partisipasi Publik Dalam Proses Anggaran Pada Ruang Lingkup Rendahnya Partisipasi Publik dalam Proses Anggaran di Indonesia - Subekti, Tri; Supriyatno, Budi; Hakim, Azis (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
The OBS Budget Transparency Survey is the world's only independent, comparative and fact-based research instrument that uses internationally recognized criteria to assess public access to central government budget information; and the role of budget monitoring institutions, such as legislative bodies and national audit bodies, in the budgeting process. In good government governance, requires accountability, transparency and community participation in every public policy determination, in order to realize good governance. The study related to public participation in the budget process was prepared with the aim of getting an overview of the implementation of public information disclosure in the budgeting process in view of the low level of public participation in the budget process in Indonesia. To achieve this goal, this study uses a qualitative method with a library research approach, namely a method of collecting data by understanding and studying theories from various literature related to the research. Public participation in the Participatory Budgeting process is a key factor.  Not everyone wants to be involved in Participatory Budgeting.  Some of the reasons that cause low community participation are the community's disappointment because they were not involved in the initial Participatory Budgeting process, Meanwhile, in countries where the level of public participation in Participatory Budgeting is quite high, Factors that encourage community involvement include very high political awareness in society at all levels, involving all levels of society, including minorities and marginalized groups